Mathematical challenge - Gardiner,Tony. (Cambridge : Cambridge university press, 1996)
This book contains almost 600 unusual and challenging multiple-choice problems designed for. The first part consists of past papers (1988-93) for the annual UK Schools Mathematical Challenge.The second part contains forty-two short papers (10 questions each) in the same style
Keywords: Mathematics -- Problems, exercises, etc